Un espejo deformante: apuntes históricos sobre la construcción jurídica de las enfermedades profesionales en Bélgica - Laurent Vogel (Universidade do Porto, 2014)
Compensation for occupational diseases is an important factor in promoting prevention at the workplace. This compensation was established in Belgium in 1927. For over 35 years, silicosis remained excluded from the list of occupational diseases, despite the fact that coal mines were an important sector of the economy and that dozens of thousands of miners were affected by it. To understand this contradiction we need to look into the social history, the social construction of medical knowledge and the legal regulation surrounding occupational diseases.